(untitled) (Annals of Medical Research, 2021)
Aim: The study was planned to determine the e-health literacy attitudes of adolescents with different socio-economic levels studying at secondary schools. Material and Methods: The study was a cross-sectional study. Descriptive Characteristics Form and e-Health Literacy Scale were used.Results: The average age of the participants is 15.98±1.10 and score average of this scale’s is 26.61±7.43. The independent variable affecting e-Health Literacy Scale were age, sex, grade and type of access internet. The children at the school with low socio-economic level have lower e-Health Literacy Scale scores than the others, younger students have lower scores than the others, girls have lower scores than boys, those with internet access from a single source have lower scores than those with access from several sources while the difference was found to be significant.Conclusion: The study found that the e-health literacy of the adolescents was at a medium level and their scale score averages with respect to sex, age, grade and socio-economic level were significantly different. Should be given particularly to the individuals with low health literacy for child and they should be informed